Belo Bellen as Compulsory Delivery in Aceh Singkil Wedding; ‘Urf and Islamic Law Anthropology Review - Khairuddin; Witro, Doli; Wiji Nurasih; Hetri Yulianti; Anisah Agustina (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
This article aims to discuss belo bellen (big betel) as a mandatory delivery for the groom to the bride in the community of Gunung Meriah District, Aceh Singkil Regency. It is delivered at the time of mengarak (providing the groom to the residence of the bride’s parents) of the wedding reception. This research is qualitative with an ethnographic approach. Data collection techniques were through in-depth interviews and observation supported by relevant literature data. Data were then analyzed qualitatively, namely through data condensation and presentation then and drawing. This research found that mandatory belo bellen delivery has been practiced for a long time and therefore becomes one of the legacies. Belo bellen take and give is made on the second night of the wedding party, attended by women. The function of belo bellen is to fulfill the custom, namely giving souvenirs of big betel to the bride’s family. The tradition is considered as a good deed according to ‘urf (Islamic legal context). In the anthropology of Islamic law, the tradition reflects the legal culture, legal behavior, and legal views of Aceh Singkil people.